2016
DOI: 10.15580/gjsetr.2016.2.061416105
|View full text |Cite
|
Sign up to set email alerts
|

Small Farm Gravity Drip Irrigation System for Crop Production

Abstract: This study involves the construction, installation and testing of a small farm gravity drip irrigation system on a land area of 900m 2 (30mx30m). It was done using a network of polyvinyl chloride (PVC) pipes of three sizes (which served as the main, submain and laterals), control valves (located on the sub main) and micro emitters (which controlled uniform application of water and fertilizer directly into the root zone of the plant by gravity). The water application uniformity of the system was determined by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Statistically, Table 6 shows significant effect of the gravity-fed drip irrigation system under study and depth of irrigated water for the period under consideration. In line with the finding of Isikwue et al (2016) [30], the wetting depth of up to 1.5 m can accommodate 0.3 -1.0 m effective rooting depth for small vegetables (such as spinach, carrot, lettuce, cabbage, garlic, onions etc. ), 0.7 -1.5 m rooting depth for vegetables of solanium family and 0.6 -1.5 m rooting depth for vegetables of cucumber family.…”
Section: Depth Of Infiltration Of Irrigated Watersupporting
confidence: 85%
“…Statistically, Table 6 shows significant effect of the gravity-fed drip irrigation system under study and depth of irrigated water for the period under consideration. In line with the finding of Isikwue et al (2016) [30], the wetting depth of up to 1.5 m can accommodate 0.3 -1.0 m effective rooting depth for small vegetables (such as spinach, carrot, lettuce, cabbage, garlic, onions etc. ), 0.7 -1.5 m rooting depth for vegetables of solanium family and 0.6 -1.5 m rooting depth for vegetables of cucumber family.…”
Section: Depth Of Infiltration Of Irrigated Watersupporting
confidence: 85%
“…Moreover, the installation of drip tape emitter in soil surface should be adjusted appropriately in order to reduce head loss in sub unit drip irrigation system. Cleaning filters on a regular basis, inspecting the pressure drop through the filter, looking over the screen holes, and flushing the laterals at least twice or three times a year could all help to prevent clogging, as also suggested by Storlie et al [14], and as described in [15].…”
Section: Discharge Rates and Emission Uniformitymentioning
confidence: 96%
“…In the case of mixed PV coupling, the best performances are obtained for solar pumps. Numerous researches on the architecture of SPAPV have shown that in order to improve the efficiency of water use, increase distribution uniformity and increase yield, at direct pumping systems (that pump water only when PV captures solar radiation) [46], water storage tanks [47] or accumulators (batteries) have to be added. The arrangements for localized irrigation with a water storage tank allow the administration of water to the plant when the energy generated by PV is not enough [48].…”
Section: Introductionmentioning
confidence: 99%